Evaluation of prostatic cancer prevalence in patients with prostatic-specific antigen between 4 and 10 and normal digital rectal examination - Tadayon, Farhad (Adv Biomed Res, 2016)
BACKGROUND: Prostate cancer is one of the most common male cancers. The prevalence of prostate cancer is different due to genetic and environmental factors. Diagnosis of prostate cancer is by biopsy due to prostate-specific antigen (PSA) and Digital Rectal Examination (DRE). Controversy about decision making for prostate biopsy in PSA between 4 and 10 and normal DRE, is one of the problems in this time. In this study we evaluated the prevalence of prostate cancer in males with PSA between 4 and 10 and normal DRE. We also evaluated the PSA density and percent of free PSA in patients with prostate cancer. MATERIALS AND METHODS: A total of 121 males with PSA between 4 and 10 and normal DRE, were evaluated. Then, transrectal ultrasonography (TRUS) andprostate biopsy from 12 points of peripheral zone, was done. These data were analyzed by Chi-square, t-test and ANOVA and Roc curve. RESULTS: In this study, the prevalence of prostate cancer in PSA between 4 and 10 and normal DRE, was evaluated, 29.8%. With use of Roc curve, PSA density cutoff point was calculated 0.12 and percent of free PSA cutoff point, was calculated, 18%. CONCLUSION: In males with PSA between 4 and 10 and normal DRE, PSA density smaller than 0.12-0.15, and percent of free PSA greater than 18%, the prevalence of prostate cancer is very few and we can safely ignore the TRUS and prostate biopsy in these males and eliminate its costs and side effects.